2013
DOI: 10.1016/j.jtbi.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

A model for intracellular actin waves explored by nonlinear local perturbation analysis

Abstract: Waves and dynamic patterns in chemical and physical systems have long interested experimentalists and theoreticians alike. Here we investigate a recent example within the context of cell biology, where waves of actin (a major component of the cytoskeleton) and its regulators (nucleation promoting factors, NPFs) are observed experimentally. We describe and analyze a minimal reaction diffusion model depicting the feedback between signalling proteins and filamentous actin (F-actin). Using numerical simulation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 52 publications
4
36
1
Order By: Relevance
“…Thus, the insights provided here are important steps towards understanding the differences between actin wave dynamics at the dorsal and ventral cell surfaces. We note that the bistability in our system stems from reaction schemes of proteins that are in or close to the level of direct interaction with actin, which is in contrast to previous works attributing bistability in the actin system to the states of upstream molecular switches, such as Rho-GTPases2551, or feedbacks in the actomyosin system52. While the model focuses on the biochemical components, it currently ignores the actual growth of the vertical, cup-shaped protrusions413294053 that may introduce additional details, such as feedback between membrane shape and actin activity162930.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, the insights provided here are important steps towards understanding the differences between actin wave dynamics at the dorsal and ventral cell surfaces. We note that the bistability in our system stems from reaction schemes of proteins that are in or close to the level of direct interaction with actin, which is in contrast to previous works attributing bistability in the actin system to the states of upstream molecular switches, such as Rho-GTPases2551, or feedbacks in the actomyosin system52. While the model focuses on the biochemical components, it currently ignores the actual growth of the vertical, cup-shaped protrusions413294053 that may introduce additional details, such as feedback between membrane shape and actin activity162930.…”
Section: Discussioncontrasting
confidence: 78%
“…There are significant feedbacks between these regulatory layers that influence cell behavior. Dynamic feedbacks from actin back onto GTPase regulation lead to the generation of dynamic waves of actin polymerization that generate force upon colliding with the cell periphery (see, e.g., Figure (c)). Imaging studies have found that a number of actin binding proteins associate with these waves .…”
Section: Broader Regulation Of Cell Bulk Behavior Through Signal Tranmentioning
confidence: 99%
“…Furthermore, they exhibit excitable characteristics such as mutual annihilation (two waves converging suppress each other), with interactions between small GTPases and actin being reported to give rise to this excitability (Figure (d) for example depicts a relationship between waves of actin activity and FBP17 activity that are out of phase with FBP17 leading the actin wave). Mata and Bernitt have further suggested that, in some cases, the unique nature of GTPases as a conserved excitable activator produces a global coupling between disparate regions of a wave. This type of ‘conserved excitable system’ has distinct wave propagation characteristics, such as size dependent propagation velocity, as observed in …”
Section: Broader Regulation Of Cell Bulk Behavior Through Signal Tranmentioning
confidence: 99%
“…In the model analyzed by Mata et al (Mata et al, 2013), the GTPase enhances its own activation by positive feedback, and is inactivated by negative feedback from F-actin. It is essential for this model that the concentration of a GTPase, i.e.…”
Section: Characteristics Of the Excitable System As Determined In Giamentioning
confidence: 99%